2022
DOI: 10.1111/jnu.12774
|View full text |Cite
|
Sign up to set email alerts
|

Web‐based self‐management intervention for patients with cancer: A meta‐analysis and systematic review

Abstract: Aim This study is conducted to synthesize the effects of web‐based self‐management intervention on patients with cancer. Evaluation We searched Web of Science, PubMed, Embase and Cochrane library databases for related randomized controlled trials from inception through 2021. Reference lists of included studies were also searched for additional qualified studies. For quantitative data synthesis, standardized mean differences were used to eliminate the influence caused by different scales. Narrative synthesis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…The use of technology is proven to affect the self-efficacy of cancer patients. (8,9) Based on level of education, some respondents have secondary education (high school, Islamic high school, vocational high school, vocational Islamic high school), that is 47 people (43.9%). Higher education will certainly affect the cognitive abilities and attitudes of cancer patients towards the treatment that will be carried out.…”
Section: Discussionmentioning
confidence: 99%
“…The use of technology is proven to affect the self-efficacy of cancer patients. (8,9) Based on level of education, some respondents have secondary education (high school, Islamic high school, vocational high school, vocational Islamic high school), that is 47 people (43.9%). Higher education will certainly affect the cognitive abilities and attitudes of cancer patients towards the treatment that will be carried out.…”
Section: Discussionmentioning
confidence: 99%
“… 53 Others suggested that e-health devices are preferable. 23 , 26 , 49 Several studies have shown that patients have difficulties initiating communication about self-care strategies with healthcare practitioners and that this is a source of dissatisfaction. 51 Patients do not feel comfortable talking about their use of self-care with healthcare practitioners, who in turn do not ask patients about self-care.…”
Section: Discussionmentioning
confidence: 99%
“…25 However, in general, several studies have shown promising effects of self-care. 20,23-27 One review 27 found that 75% of the included trials revealed a positive effect of the self-care activities physical activity, cognitive distraction, and increased recovery, that is, relaxation. Overall, there appears to be at least one effective self-care strategy for each of the symptoms 20 experienced by the currently studied patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations